How are countries supporting health workers? Data from the COVID-19 Health System Response Monitor. (20th October 2021) - Williams, G; Scarpetti, G; Bezzina, A; Vincenti, K; Grech, K; Kowalska-Bobko, I; Sowada, C; Furman, M; Gałązka-Sobotka, M; Maier, CB
Abstract: Background: Health workers have been at the forefront of treating and caring for patients with COVID-19. They were often under immense pressure to care for severely ill patients with a new disease, under strict hygiene conditions and with lockdown measures creating practical barriers to working. This study aims to explore the range of mental health, financial and other practical support measures that 36 countries in Europe and Canada have put in place to support health workers and enable them to do their job. Methods: We use data extracted from the COVID-19 Health Systems Response Monitor (HSRM). We only consider initiatives implemented outside of clinical settings where COVID-19 patients are treated, and therefore exclude workplace provisions such as availability of personal protective equipment, working time limits or mandatory rest periods. Results: We show that countries have implemented a range of measures, ranging from mental health and well-being support initiatives, to providing bonuses and temporary salary increases. Practical measures such as childcare provision and free transport and accommodation have also been implemented to ensure health workers can get to their workplace and have their children looked after. Other initiatives such as offering continuing professional development credits for knowledge learnt during the crisis were also offered in some countries, albeit less frequently. Conclusions: While a large number of initiatives have been introduced, often as ad-hoc measures, their effectiveness in helping staff is unknown in most countries. The effectiveness of these initiatives should be evaluated to inform future crisis responses and strategies for health workforce development.